The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1979
DOI: 10.1073/pnas.76.5.2405
|View full text |Cite
|
Sign up to set email alerts
|

Immunological tolerance: High-dose antigen-induced suppressor cells from tolerant animals inactivate antigen-presenting macrophages

Abstract: Studies were carried out to characterize the target cell for the activity of suppressor cells induced in highzone tolerance to deaggregated human gamma globulin (HGG). We applied an in vitro system for the initiation of an immune response, consisting of culturing spleen Iymphocytes on HGG-fed macrophages, in which initiator T cells are generated.These cells, when injected into the foot pads of syngeneic mice, recruit specific anti-HGG effector T Iymphocytes. We Although all three models are strictly antigen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…In general the targets of Ts are thought to be helper T cell [18] or B cell [19], but some investigators suggest that macrophages are also targets of Ts [7,8]. Accord ing to the results obtained in figures 3 and 5, we show that Ts induces the reduction of antigen presenting activity of SACs, in other words, SACs are one of the targets ofTs.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In general the targets of Ts are thought to be helper T cell [18] or B cell [19], but some investigators suggest that macrophages are also targets of Ts [7,8]. Accord ing to the results obtained in figures 3 and 5, we show that Ts induces the reduction of antigen presenting activity of SACs, in other words, SACs are one of the targets ofTs.…”
Section: Discussionsupporting
confidence: 63%
“…The importance of antigen presenting cells in the initiation of immune responses is widely acknowledged [4][5][6]. Some investi gators have demonstrated that antigen presentation by macrophages is reduced in immunologically toler ant animals [7,8], Antigen presenting cells in tolerant animals is not, however, thoroughly studied.…”
Section: Introductionmentioning
confidence: 99%
“…Another precedent for the suggestion that Tc may regulate expression of Ig in vivo is the demonstration of Segal et al (33) that T cells from high zone tolerant mice could kill macrophages pulsed with the tolerizing antigen . However, Abbas et al (34)(35)(36) have shown recently that suppression and cytotoxicity may operate by quite different mechanisms at the level of the target cell .…”
Section: Discussionmentioning
confidence: 99%
“…These factors inhibit the generation of PFC activity following immunization with sheep erythrocates. A high dose of R3230 AdCa-associated antigen may also induce suppressor cells from tolerant cells which inactivate antigen presenting macrophages, leading to a decline in the host cell-mediated immunity (Segal et al, 1979).…”
Section: Discussionmentioning
confidence: 99%